Ambient volatile organic compounds (VOCs) in communities of the Athabasca oil sands region: Sources and screening health risk assessment. (April 2018) - Bari, Md. Aynul; Kindzierski, Warren B.
Abstract: An investigation of ambient levels and sources of volatile organic compounds (VOCs) and associated public health risks was carried out at two northern Alberta oil sands communities (Fort McKay and Fort McMurray located < 25 km and >30 km from oil sands development, respectively) for the period January 2010–March 2015. Levels of total detected VOCs were comparatively similar at both communities (Fort McKay: geometric mean = 22.8 μg/m 3, interquartile range, IQR = 13.8–41 μg/m 3 ); (Fort McMurray: geometric mean = 23.3 μg/m 3, IQR = 12.0–41 μg/m 3 ). In general, methanol (24%–50%), alkanes (26%–32%) and acetaldehyde (23%–30%) were the predominant VOCs followed by acetone (20%–24%) and aromatics (∼9%). Mean and maximum ambient concentrations of selected hazardous VOCs were compared to health risk screening criteria used by United States regulatory agencies. The Positive matrix factorization (PMF) model was used to identify and apportion VOC sources at Fort McKay and Fort McMurray. Five sources were identified at Fort McKay, where four sources (oil sands fugitives, liquid/unburned fuel, ethylbenzene/xylene-rich and petroleum processing) were oil sands related emissions and contributed to 70% of total VOCs. At Fort McMurray six sources were identified, where local sources other than oil sands development were also observed. Contribution of aged air mass/regional transport including biomass burning emissions was ∼30% of total VOCs at both communities. Source-specific carcinogenic and non-carcinogenic risk values were also calculated and were below acceptable and safe levels of risk, except for aged air mass/regional transport (at both communities), and ethylbenzene/xylene-rich (only at Fort McMurray). Graphical abstract: Image 1 Highlights: Sources and health risks of ambient VOCs assessed at two oils sands communities. Four oil sands related sources contributed to 70% of total VOCs at Fort McKay. Contribution of aged air mass/regional transport (natural/anthropogenic) was ∼30%. Aged air mass/regional transport and ethylbenzene/xylene-rich important to cancer risk. Findings are useful for developing risk management actions for controlling VOCs. Abstract : Sources and associated human health risks of VOCs assessed at Canadian oil sands communities for air quality management.